A utopia da (re)integração: o potencial do trabalho prisional no Brasil - Manfrin, Flávio Antônio (Universidade do Vale do Rio dos Sinos, 2022)
This thesis argues that penitentiary policies, aimed at working in prison, based on the theoretical narrative of retributive justice, are insufficient in face of the demands of the social (re)integration of inmates. However, restorative justice is consistent with the social pretensions of guaranteeing fundamental rights, protection of the person and commitment to the solidification of citizenship, arguing that the formulation of reintegrative policies is founded on the observation of conceptual elements in the recent literature about the theme. That is proven, in view of the survey carried out, in documentary form, in the prisons of the 27 Brazilian states. Confronted with the model adopted in the Chapecó Prison Complex (CPC), in the State of Santa Catarina, it shows the possibility of (re)integration supported by the argument of the autonomy of the social actors involved in the process. Evidence, identified, even if incipient, emerged in the Santa Catarina prison system in 1940, by State Law N. 3,308 (SANTA CATARINA, 1963), which became part of the Brazilian Penal Code, but which was only legitimated in the Penal Execution Law – LEP (BRASIL, 1984) –, if concretized in the Federal Constitution of 1988 (BRASIL, 1988). In this sense, the thesis argues that (re)integration through work is carried out based on shared actions, autonomy in management and commitment to human rights, articulated with other criminal alternatives that promote extrication. The bibliography is based on considerations from the classics of literature represented by Michel Foucault (2014). In Brazil, Sergio Adorno (1991), as well as Bitencourt (2007), brought to the heart of the discussion polemics around the concept of resocialization. Thus, we present that the purpose attributed to the modern prison is based on the concept of criminal execution provided for in the LEP. Although the literature reveals the existence of controversies around the subject of resocialization.
Keywords: Sistema prisional; (Re)integração pelo trabalho; Gestão cooperativa; Políticas públicas; Trabalho prisional; Prison system; (Re)integration through work; Cooperative management; Public policies; Prison work; ACCNPQ::Ciências Humanas::Sociologia